2023
DOI: 10.1002/jmv.28576
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress—A key determinant of complications and negative outcome in hepatitis E virus infected pregnancies: A comprehensive account involving cases from northeast India

Abstract: Regulated oxidative stress (OS) is important during pregnancy. Sporadic studies suggest the significance of deregulated OS in hepatitis E virus (HEV) infected pregnancy, but with limited reactive oxygen species (ROS) or antioxidant markers. The present novel study, therefore, aimed to evaluate the significance of ROS‐antioxidant imbalance and resulting altered OS in HEV infected pregnancy complications like preterm delivery (PTD) and outcome. Difference in serum levels of ROS and antioxidant panel of markers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(88 reference statements)
0
0
0
Order By: Relevance
“…NO-produces the NO-synthase enzyme. There are three types of NO-synthase (NOS) isozymes in mammals including endothelial NO-synthase, neuronal NO-synthase, and inducible NO-synthase (Kashyap et al, 2023).…”
Section: Fig 1 Free Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…NO-produces the NO-synthase enzyme. There are three types of NO-synthase (NOS) isozymes in mammals including endothelial NO-synthase, neuronal NO-synthase, and inducible NO-synthase (Kashyap et al, 2023).…”
Section: Fig 1 Free Radicalsmentioning
confidence: 99%
“…The components of the antioxidant protection system are considered to be: electron acceptors -vitamins E and K 3 ; acceptors of superoxide radical anions -methionine, cysteine; scavengers of hydroxyl radicals -aliphatic alcohols; factors of elimination of toxic products of LPO tocopherol (TF), ionol, superoxide dismutase, glutathione peroxidase system; metal chelators with variable valence (complexons). Components of antioxidant protection are divided into hydrophilic and hydrophobic, enzymatic (catalase, superoxide dismutase, glutathione peroxidase system, glutathione, ascorbic acid, adrenaline, serotonin, tocopherols, retinoids, flavonoids, phospholipids, ceruloplasmin) and non-enzymatic (Kashyap et al, 2023).…”
Section: System Of Antioxidant Protectionmentioning
confidence: 99%
“…HEV infection aggravates oxidative stress during pregnancy [163]. Lower GSH levels are observed in pregnant women with an HEV infection having preterm delivery and low birthweight newborns compared to healthy pregnant women [143,144]. It is suggested that the GSH level may be used for risk stratification in HEV infection during pregnancy [163].…”
Section: Hepatitis E Virus (Hev) and Hepatitis A Virus (Hav)mentioning
confidence: 99%